Anti-Doping Education and Prevention Strategies among Athletes: A Narrative Review - Aghniya Faza; Dinda Amalia; Farrel Wicaksono; Romadhiyana Kisno Saputri (Journal of Sports Medicine and Physiotherapy, 2026)
Background: Doping is a major problem in competitive sport, despite stringent anti-doping policies. Recent evidence reveals education is a key preventative approach to enhancing athletes’ awareness, ethical decision-making and long-term engagement with clean sport.Objective: This narrative review intended to consolidate the available research on anti-doping education, athletes’ understanding and prevention tactics in sport.Methods: A narrative literature review was performed using the Scopus database. We selected papers published in English between 2020 and 2025 using keywords linked to anti-doping, education, intervention, and athletes. Fifteen papers were included in the final narrative synthesis according to pre-defined inclusion and exclusion criteria.Results: Athletes’ anti-doping awareness remains inconsistent among athletic demographics despite past exposure to education. Values-based education, anti-doping literacy and athlete-centred educational approaches were consistently more effective than information-based initiatives in the improvement of knowledge, ethical awareness and decision-making . The review also found dietary supplement use was a key contributor to inadvertent doping, highlighting the need for supplement risk education and evidence-based decision making. In addition, sustained anti-doping prevention requires ongoing education, multidisciplinary stakeholder involvement and instructional initiatives customized to particular athlete groups.Conclusion: Anti-doping education should go beyond knowledge transmission and cover ethical values, anti-doping literacy, supplement awareness and context appropriate educational tactics. Continuous, multidisciplinary, and evidence-based educational initiatives are needed to improve clean sport and reduce the number of purposeful and unintentional anti-doping rule infractions.